Necessary conditions for continuous-time optimization under the Mangasarian–Fromovitz constraint qualification. (2nd April 2020) - do Monte, Moisés Rodrigues Cirilo; de Oliveira, Valeriano Antunes
ABSTRACT: In this paper, a Mangasarian–Fromovitz-type regularity condition is presented with the purpose of obtaining first order necessary optimality conditions for continuous-time nonlinear programming problems with both equality and inequality constraints. The Karush–Kuhn–Tucker-type optimality conditions are obtained by means of geometric ideas, where a theorem of the alternative and a uniform implicit function theorem are the main tools.